THE COMMUNITY PERCEPTION OF MANGROVE CULTURAL SERVICES IN XUAN THUY NATIONAL PARK VIETNAM: Received: 14th February 2022; Revised: 03rd June 2022, 10th June 2022, 27th June 2022; Accepted: 30th June 2022 - Ha, Hue Thi Thu; Hoang, Thang Van; Do, Huynh Nhat; Luong, Hai Quoc (PEOPLE: International Journal of Social Sciences, 2022)
The need to save mangroves is growing, however, debasement has persisted for decades, because the processes of decision-making are inefficient, found solely on economic factors. This study provides a tool for mangrove conservation and management to explore the socio-cultural values ​​of mangrove ecosystem services through research in Xuan Thuy National Park, one of nine Ramsars in Vietnam, and also an area heavily affected by shrimp farming. 150 households were selected for an interview, 5 focus group discussions in 5 buffer zone communes, 10 in-depth interviews were carried out to find out the ecosystem services that mangroves provide, compared with literature review, and 3 cultural services listed by the local people as the characteristics of the mangroves here are lifestyle change, strengthening family relationship, implicit division of labor in the community. This proves that local people are ambassadors connecting the mangroves and the government. This finding suggests that the socio-cultural aspect of mangrove services should be deliberated by policymakers as a measure of great concern when facing the challenges of wetland ecosystem conservation.